The Evolving World of Chronic Kidney Disease Mineral Bone Disorder - Antonio Bellasi (European Medical Journal Nephrology, 2013)
Chronic kidney disease – mineral and bone disorder (CKD-MBD) is associated with a significant morbidity and mortality. In vitro and animal models suggest that phosphorous, calcium, parathyroid hormone, and vitamin D abnormalities, mediate the cardiovascular and bone diseases that characterise CKD-MBD and increase the risk of death. Currently, mineral abnormalities are corrected through phosphorous restriction, phosphate binders, calcimimetics and vitamin D administration. Nonetheless, data in humans that support the use of these compounds are still scarce, mainly based on observational studies. Thus, a considerable number of doubts and questions still challenge clinicians dealing with CKD patients and mineral metabolism imbalances. We herein critically review clinical evidence that support the use of different drugs in CKD-MBD.